2016
DOI: 10.1002/jsfa.7985
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of lactobiopolymer-montmorillonite composites for dip coating applications on fresh strawberries

Abstract: The addition of nanofillers, such as MMT, into protein-based coating could improve its water vapour barrier and could affect, positively, some parameters of the shelf life of coated strawberries. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
(88 reference statements)
1
7
0
Order By: Relevance
“…Different letters a-c indicates significant differences among treatments during storage period at p \ 0.05 and CS are effective in controlling postharvest contamination. Our findings are in agreement with previous studies where antimicrobial coating effectively controlled YM count throughout storage (Junqueira-Gonçalves et al, 2017;Nasrin et al, 2017;Treviño-Garza et al, 2015;Valenzuela et al, 2015). It is known that CS-based antimicrobial coating possess a protective effect against YM growth on fresh fruits and vegetables (Vu et al, 2011).…”
Section: Microbiological Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Different letters a-c indicates significant differences among treatments during storage period at p \ 0.05 and CS are effective in controlling postharvest contamination. Our findings are in agreement with previous studies where antimicrobial coating effectively controlled YM count throughout storage (Junqueira-Gonçalves et al, 2017;Nasrin et al, 2017;Treviño-Garza et al, 2015;Valenzuela et al, 2015). It is known that CS-based antimicrobial coating possess a protective effect against YM growth on fresh fruits and vegetables (Vu et al, 2011).…”
Section: Microbiological Analysissupporting
confidence: 93%
“…It was found that the count of YM was increased (p \ 0.05) specifically for control (2.34 and 6.49 log CFU/fruit) and in strawberries coated with antimicrobials (2.26 and 5.28 log CFU/fruit for CS and 2.22 and 5.04 log CFU/fruit for CS-MFA). This increase in the growth of YM can be explained by the fact that strawberries are prone to high levels of YM pathogen contamination compared to other fruits because they possesses: (1) high levels of sugars and nutrients; (2) optimal water activity and pH for fungal growth; and (3) a soft skin that can be easily ruptured for microorganisms to proliferate (Junqueira- Gonçalves et al, 2017;Vu et al, 2011). CS-MFA was effectively (p \ 0.05) control the count of YM when compared to the counterpart CS and control throughout the storage.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Thus, the MMT15A contributed to the increase in the film residue at 800°C. Clay has good thermal stability; thus, it can strengthen the polymer structure and prevent the heat to expand quickly, thus preventing further degradation, acting as a temperature barrier and contributing to the retention of volatile compounds and weight loss (Hwang et al, 2013; Junqueira‐Gonçalves, Salinas, Bruna, & Niranjan, 2017). A greater diffusion was observed in the films containing tocopherol and MMT15A.…”
Section: Resultsmentioning
confidence: 99%
“…The Group 3 was composed of films made with the addition of MMT15A and tocopherol, corresponding to the Formulations 6, 7, and 8, which exhibited higher polymer residue at 800 C (res) and diffusion coefficient (D), with the vectors displayed near the MMT15A vector. Thus, the MMT15A contributed to the increase in the film residue at 800 C. Clay has good thermal stability; thus, it can strengthen the polymer structure and prevent the heat to expand quickly, thus preventing further degradation, acting as a temperature barrier and contributing to the retention of volatile compounds and weight loss (Hwang et al, 2013;Junqueira-Gonçalves, Salinas, Bruna, & Niranjan, 2017). A greater diffusion was observed in the films containing tocopherol and MMT15A.…”
Section: Overall Characterization By Pcamentioning
confidence: 99%
“…The use of starch nanoparticles incorporated into coating film together with a modified atmosphere led to the enhanced total antioxidant activity, volatiles, and organic acids maintaining of FCC. Junqueira-Goncalves et al evaluated the effect of addition of MMT-NPs to a lacto-biopolymer coating [ 125 ]. They found that the material could improve its water vapor barrier and reduce weight loss, as well as oxygen uptake and the release of carbon dioxide, and improve fruit firmness and reduce mold and yeast load, at last prolong the shelf-life of coated strawberries.…”
Section: Inorganic and Metal Oxide Nanomaterials Applied In Food Pmentioning
confidence: 99%